VD_FINDINFO HC / 2009 / 359 vom 4. November 2009 - VD Tribunal cantonal (2009)
SOCIÉTÉ SIMPLE, DISSOLUTION DE LA SOCIÉTÉ, FIN, LIQUIDATIONEN GÉNÉRAL | 545 al. 1 ch. 1 CO, 545 al. 1 ch. 4 CO, 489 CPC, 568 CPC, 573 CPC, 574 CPC, 586 CPC, 596 CPC, 1 ch. 18 LVCO